Mobile App for Child Learning with Task Reminders and Performance Statistics - Setyadinsa, Radinal; Pinastawa, I Wayan Rangga; Razaqa, Dhi'Fan; Sebayang, Axel Putra Bintang Syahkuala (Program Studi Informatika, 2025)
The rapid development of mobile technology has opened significant opportunities to support education, particularly in monitoring children